Gingival Tissue Human Beta-Defensin Levels in Relation to Infection and Inflammation - Meltem Özdemir; Feriha Caglayan; Floris J. Bikker; Pirkko Pussinen; Eija Könönen; Nermin Yamalik; Mervi Gürsoy; Dareen Fteita; Kamran Nazmi; Guliz N. Güncü; Milla Pietiäinen; Mimmi Tolvanen; et al. (My University, 2022)
Aim
To profile gingival tissue levels of human beta‐defensin (hBD)‐2 and hBD‐3 in relation to gingival inflammation, Th17‐related cytokine concentrations, Porphyromonas gingivalis counts, and gingipain and total protease activities.
Materials and Methods
Gingival tissue and subgingival plaque samples were collected from 21 periodontitis patients including 48 periodontal pocket sites with marginal, mild, or moderate to severe inflammation. hBD levels were determined by immunodetection, P. gingivalis counts with real‐time polymerase chain reaction, protease activities with fluorogenic substrates, and cytokine concentrations with Luminex technique. Data were statistically analysed using Kruskal–Wallis and Mann–Whitney U tests and Spearman correlation coefficients.
Results
Subgingival plaque counts of P. gingivalis (p = .001) and gingipain activity (p < .001), as well as interleukin (IL)‐1β (p = .012), IL‐10 (p = .024), IL‐17A (p = .002), IL‐17F (p = .006), and IL‐23 (p = .036) concentrations were elevated in severely inflamed sites, whereas no change was observed in hBD‐2 and hBD‐3 levels. Negative correlations were found between protease activity and hBD‐2 (p = .033) and hBD‐3(p = .003) levels.
Conclusions
Shift in gingival inflammation from marginal to mild stage is related to elevations in subgingival plaque P. gingivalis counts and gingipain activity, but not to tissue hBD levels. Negative correlations between hBDs and total protease activity suggest the degradation of these antimicrobial peptides in progressed inflammation.